Hungarian Monitoring, 31 July 1990 . [Magyar rádiófigyelő], 1990. július 31 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Danube-Adriatic summit in Venice - Shevardnadze-Baker meeting - Latest Ukrainian demands Domestic Affairs: - New presidents at Hungarian Radio and Hungarian Television - Tölgyessy-Kónya debate over the constitution - Canadian army chief of staff arrives in Budapest Economy: - New leaders in Hungarian state enterprises - "Népszabadság" (People's Freedom daily paper) stock company formed - Drastic price increases Külpolitika: - Duna-Adria csúcstalálkozó Velencében - Sevardnadze-Baker találkozó - Újabb ukrán követelések Belpolitika: - Új elnökök a Magyar Rádió és a Magyar Televízió élén - Tölgyessy-Kónya vita az alkotmányról - Budapestre érkezett a kanadai fegyveres erők vezérkari főnöke Gazdaság: - Vezetőcserék magyar állami vállalatoknál - Megalakult a Népszabadság Rt. - Drasztikus áremelkedések